KAJIAN KEPUSTAKAAN: PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE STAD TERHADAP HASIL BELAJAR SISWA PADA MATERI MAKNA NEGARA KESATUAN REPUBLIK INDONESIA KELAS IV SD - Lestari, Nanda Ayu; Simbolon, Naeklan; Nurmayani, Dr.; Faisal, F; Siregar, Waliyul Maulana (Universitas Negeri Medan, 2024)
This research aims to determine the effect of student learning outcomes using the STAD type cooperative learning model on the material on the meaning of the Unitary State of the Republic of Indonesia in class IV SDN 106810 Sampali T.A 2023/2024. This research uses quantitative research methods. The type of research is Quasi Experiment in the form of Nonequivalent Multiple Group Design. The population and sample in this research were class IV students at SDN 106810 Sampali, totaling 40 students. This research sample uses a sample sampling technique. The tool used in data collection in this research was a multiple choice test. The data analysis technique in this research uses hypothesis testing using the t-test. Based on data analysis, the average value of learning outcomes for the STAD learning model is 82.25 and the value of learning outcomes using the conventional model is 77.25. From the test results of the data analysis requirements, the population is normally distributed and has a homogeneous variance and the results of hypothesis testing obtained a value of Sig. 0.000 where the Sig value. < (0.05), indicating H0 is rejected and Ha is accepted. So it can be concluded that there is an influence using the STAD model on student learning outcomes in the material on the meaning of the Unitary State of the Republic of Indonesia in class IV SDN 106810 Sampali T.A 2023/2024.